2021
DOI: 10.1371/journal.pgen.1009705
|View full text |Cite
|
Sign up to set email alerts
|

A Y-linked anti-Müllerian hormone type-II receptor is the sex-determining gene in ayu, Plecoglossus altivelis

Abstract: Whole-genome duplication and genome compaction are thought to have played important roles in teleost fish evolution. Ayu (or sweetfish), Plecoglossus altivelis, belongs to the superorder Stomiati, order Osmeriformes. Stomiati is phylogenetically classified as sister taxa of Neoteleostei. Thus, ayu holds an important position in the fish tree of life. Although ayu is economically important for the food industry and recreational fishing in Japan, few genomic resources are available for this species. To address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 110 publications
0
19
0
Order By: Relevance
“…In our study, based on chromosome-scale genome assemblies of many Pangasiid species, transcriptomic data (Pasquier et al, 2016) and sex-linkage analyses, we identified a male-specific duplication of the amhr2 (amhr2by) gene as a potentially conserved male MSD gene in that fish family. The role of Amhr2 as an MSD gene has been functionally characterized in the tiger pufferfish, Takifugu rubripes and ayu, Plecoglossus altivelis (Kamiya et al, 2012;Nakamoto et al, 2021), and strongly suggested by sex-linkage information in common seadragon, Phyllopteryx taeniolatus, alligator pipefish, Syngnathoides biaculeatus (Qu et al, 2021), other species of pufferfishes (Duan et al, 2021;Gao et al, 2020;Kamiya et al, 2012) and yellow perch, Perca flavescens (Feron et al, 2020). In addition, the anti-Müllerian hormone, Amh, which is the cognate ligand of AmhR2, has also been demonstrated or suggested as an MSD gene in a few fish species (Hattori et al, 2012;Li et al, 2015;Pan et al, 2019Pan et al, , 2021Song et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, based on chromosome-scale genome assemblies of many Pangasiid species, transcriptomic data (Pasquier et al, 2016) and sex-linkage analyses, we identified a male-specific duplication of the amhr2 (amhr2by) gene as a potentially conserved male MSD gene in that fish family. The role of Amhr2 as an MSD gene has been functionally characterized in the tiger pufferfish, Takifugu rubripes and ayu, Plecoglossus altivelis (Kamiya et al, 2012;Nakamoto et al, 2021), and strongly suggested by sex-linkage information in common seadragon, Phyllopteryx taeniolatus, alligator pipefish, Syngnathoides biaculeatus (Qu et al, 2021), other species of pufferfishes (Duan et al, 2021;Gao et al, 2020;Kamiya et al, 2012) and yellow perch, Perca flavescens (Feron et al, 2020). In addition, the anti-Müllerian hormone, Amh, which is the cognate ligand of AmhR2, has also been demonstrated or suggested as an MSD gene in a few fish species (Hattori et al, 2012;Li et al, 2015;Pan et al, 2019Pan et al, , 2021Song et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The duplication and origin of amhr2Y pre‐dates the split between Amphilophus and Archocentrus , where it has undergone a turnover and secondary rearrangement. Y‐specific copies of amhr2 have emerged at least five times independently as the MSD gene in teleosts (Kamiya et al, 2012; Nakamoto et al, 2021; Qu et al, 2021; Feron et al, 2020; see Table ). We successfully generated a high‐contiguity haplotypic assembly of a male and assembled the complete YSR using a combination of PacBio HiFi and Bionano optical maps.…”
Section: Discussionmentioning
confidence: 99%
“…However, the discovery and assembly of SDRs has been facilitated recently due to advances in long‐read sequencing technologies (Palmer et al, 2019; Sember et al, 2021). Long‐read methodologies are especially useful to assemble SDRs, as they generate scaffolds spanning complex genomic regions (Fraser et al, 2020; Nakamoto et al, 2021; Peichel et al, 2020; Qu et al, 2021; Tao, Xu, et al, 2021; Xue et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classic theory predicts that homomorphic proto sex chromosomes evolved from ordinary autosomes by acquiring sex-determining gene/genes. Sex-determining gene/genes can be derived from gene mutation (Kamiya et al, 2012;Koyama et al, 2019), gene duplication (Li et al, 2015), and gene translocation (Nakamoto et al, 2021). Subsequently, sexually antagonistic alleles (genes with different fitness in males and females) accumulate around sexdetermining gene/genes and spread along the sex chromosomes.…”
Section: Sex Chromosome Evolutionmentioning
confidence: 99%